2020
DOI: 10.1038/s41598-020-70273-x
|View full text |Cite
|
Sign up to set email alerts
|

Marine heatwaves and the collapse of marginal North Atlantic kelp forests

Abstract: Extreme climatic events including marine heatwaves (MHWs) are becoming more frequent and severe in the Anthropocene. However, our understanding of how these events affect population dynamics of ecologically important species is limited, in part because extreme events are rare and difficult to predict. Here, we quantified the occurrence and severity of MHWs over 60 years in warm range edge kelp forests on both sides of the North Atlantic. The cumulative annual intensity of MHWs increased two-to four-fold during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 69 publications
2
100
0
Order By: Relevance
“…Above all, temperature is the most important range-limiting factor for marine macrophytes (Jueterbock et al, 2013;Repolho et al, 2017;Assis et al, 2018;Duarte et al, 2018;Martínez et al, 2018). Rising ocean temperatures, interfering with reproduction, development, and growth (Breeman, 1990;Short and Neckles, 1999), are fundamentally altering genetic diversity and adaptability Gurgel et al, 2020), and devastating macroalgal forests and seagrass meadows around the globe (Arias-Ortiz et al, 2018;Filbee-Dexter et al, 2020;Smale, 2020). In response, large-scale restoration efforts aim to avert severe ecological and economic consequences (Eger et al, 2020;Fredriksen et al, 2020;Layton et al, 2020;Tan et al, 2020;Vergés et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Above all, temperature is the most important range-limiting factor for marine macrophytes (Jueterbock et al, 2013;Repolho et al, 2017;Assis et al, 2018;Duarte et al, 2018;Martínez et al, 2018). Rising ocean temperatures, interfering with reproduction, development, and growth (Breeman, 1990;Short and Neckles, 1999), are fundamentally altering genetic diversity and adaptability Gurgel et al, 2020), and devastating macroalgal forests and seagrass meadows around the globe (Arias-Ortiz et al, 2018;Filbee-Dexter et al, 2020;Smale, 2020). In response, large-scale restoration efforts aim to avert severe ecological and economic consequences (Eger et al, 2020;Fredriksen et al, 2020;Layton et al, 2020;Tan et al, 2020;Vergés et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the current context of climate change, ocean warming implies a global impact on coastal benthic communities and especially on marine forests (Wernberg et al 2013;Filbee-Dexter et al 2020;Smale 2020), producing the decline of fucoids and their displacement to cold waters (Wernberg et al 2011). Regional studies have shown the negative effect of warming on brown macroalgae (Sansón et al 2013).…”
Section: Possible Causes and Impactsmentioning
confidence: 99%
“…Various studies have shown that macroalgae, especially canopyforming species, are threatened by rising temperatures (Smale, 2020). Furthermore, marine heatwaves have also shown significant impacts on coastal macroalgal formations (Frölicher and Laufkötter, 2018;Filbee-Dexter et al, 2020;Verdura et al, 2021). These extreme events are likely given the projected climate change scenarios (Filbee-Dexter et al, 2020).…”
Section: Climate Change-related Effects Ocean Warmingmentioning
confidence: 99%
“…Furthermore, marine heatwaves have also shown significant impacts on coastal macroalgal formations (Frölicher and Laufkötter, 2018;Filbee-Dexter et al, 2020;Verdura et al, 2021). These extreme events are likely given the projected climate change scenarios (Filbee-Dexter et al, 2020). In the context of tropicalization, which the region currently finds itself (Freitas et al, 2019), the role of rising temperatures and marine heatwaves could be one of the main impacts for marine forests.…”
Section: Climate Change-related Effects Ocean Warmingmentioning
confidence: 99%